Peran Power, Distance, dan Rank of Imposition dalam Variasi Strategi Ketidaksantunan di Pasar Tradisional Sukoharjo - Anisah Hanif; Djatmika Djatmika; Rahmaditya Khadifa Abdul Rozzaq Wijaya (Universitas Indraprasta PGRI, 2023)
Language phenomena related to the use of impoliteness strategies are always associated with efforts to do FTA. This study aims to find out the role of context theory (power, distance, and rank of imposition) in various language impoliteness strategies in Sukoharjo traditional markets. This pragmatic research by reviewing three dimensions of context is descriptive qualitative research. The data are in form of direct speech between sellers and buyers which accommodate impolite strategies in Javanese regarding overall market situation including transaction and non-transaction activities. The results of this study are the level of power based on social status and class, speech situations role, age, gender, and physical strength. All of these parts affect the power that speakers have based on the context of speech event. The imposition rank found in the buyer's strategies because more buyers have a positive desire to interact and transact in language situations. These three major context factors greatly influence the appearance of data on the use of impolite strategies in speech situations in the Sukoharjo traditional market.Keywords: Impoliteness act, power, distance, imposition rank, traditional market